A Silica Bilayer Supported on Ru(0001): Following the Crystalline‐to Vitreous Transformation in Real Time with Spectro‐microscopy. Issue 26 (15th April 2020) - Klemm, Hagen W.; Prieto, Mauricio J.; Xiong, Feng; Hassine, Ghada B.; Heyde, Markus; Menzel, Dietrich; Sierka, Marek; Schmidt, Thomas; Freund, Hans‐Joachim
Abstract: The crystalline‐to‐vitreous phase transformation of a SiO2 bilayer supported on Ru(0001) was studied by time‐dependent LEED, local XPS, and DFT calculations. The silica bilayer system has parallels to 3D silica glass and can be used to understand the mechanism of the disorder transition. DFT simulations show that the formation of a Stone–Wales‐type of defect follows a complex mechanism, where the two layers show decoupled behavior in terms of chemical bond rearrangements. The calculated activation energy of the rate‐determining step for the formation of a Stone—Wales‐type of defect (4.3 eV) agrees with the experimental value. Charge transfer between SiO2 bilayer and Ru(0001) support lowers the activation energy for breaking the Si−O bond compared to the unsupported film. Pre‐exponential factors obtained in UHV and in O2 atmospheres differ significantly, suggesting that the interfacial ORu underneath the SiO2 bilayer plays a role on how the disordering propagates within the film. Abstract : Real‐time studies of the crystalline‐to‐vitreous conversion rate of a SiO2 bilayer supported on Ru(0001) reveal an apparent activation energy of 4.2 eV for the process. DFT simulations suggest the formation of a Stone–Wales‐type defect as the starting point for the transformation.